2020
DOI: 10.1016/j.corsci.2020.108875
|View full text |Cite
|
Sign up to set email alerts
|

High temperature oxidation and embrittlement at 500–600 °C of Ti-6Al-4V alloy fabricated by Laser and Electron Beam Melting

Abstract: The oxidation kinetics of Ti-6Al-4V alloys fabricated by LBM and EBM, HIP-treated or not, are similar to that of a rolled annealed Ti-6Al-4V alloy, as regards oxide layer and oxygen diffusion layer thickness. Kinetics of oxygen ingress in the metal is independent of the alloy microstructure. At room temperature, the thickness of the brittle layer after a tensile test corresponds to the oxygen diffusion layer, with an oxygen concentration above a critical value that is clearly below 1 at %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 73 publications
3
25
0
Order By: Relevance
“…This leads to the conclusion that grain size has little or no effect on oxygen diffusion. The same conclusions were drawn by Casadebaigt et al on a TA6V alloy made by additive manufacturing [17]. For these alloys manufactured using electron and laser beam melting, authors reported that a hot isostatic pressure (HIP) treatment did not have an effect on mass variations nor on oxygen diffusion coefficients, despite an important coarsening of the microstructure resulting from the HIP.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…This leads to the conclusion that grain size has little or no effect on oxygen diffusion. The same conclusions were drawn by Casadebaigt et al on a TA6V alloy made by additive manufacturing [17]. For these alloys manufactured using electron and laser beam melting, authors reported that a hot isostatic pressure (HIP) treatment did not have an effect on mass variations nor on oxygen diffusion coefficients, despite an important coarsening of the microstructure resulting from the HIP.…”
Section: Introductionsupporting
confidence: 71%
“…Excessively high temperatures can modify oxidation regimes, as shown in Ti6242 and Ti6242S alloys by Calvert and Kosaka and Gaddam et al, respectively [13,15]. This can also lead to modified contents of alloying elements between phases, as found in the TA6V alloy [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…This is in good agreement with the literature values determined for Ti6Al4V in a similar temperature range. [ 52,53 ]…”
Section: Discussionmentioning
confidence: 99%
“…This is in good agreement with the literature values determined for Ti6Al4V in a similar temperature range. [52,53] After the two-step process, the diffusion depth is enhanced to 85 μm. The reduced oxygen concentration at the gassubstrate interface compared with the single-step process indicates that the oxide layer completely dissolved before the end of the second process step and thus could no longer serve as oxygen reservoir.…”
Section: Oxygen Diffusion Zonementioning
confidence: 99%
“…This function is highly helpful in the manufacture of titanium-6aluminium-4vanadium (Ti6Al4V) parts since it is possible to monitor the small amounts of interstitial components during manufacturing [69]. Besides, a high temperature of around 700 degrees Celsius is established in the system throughout the construction of the component to decrease excess tensions and thereby warpage and distortion [70].…”
Section: Electron Beam Meltingmentioning
confidence: 99%